Humanitarian Crisis: Preventing Bullying Through Civic Education - Pradanna, Satrio Alpen (Proceeding International Conference on Religion, Science and Education, 2025)
The frequent occurrences of bullying in school environments indicate that students today are less inclined to practice Pancasila values, particularly the second principle of “Kemanusian yang adil dan beradab (just and civilized humanity).” This research aims to examine the role of Civic Education in preventing bullying in schools. The research method used is a qualitative approach with content analysis, analyzing Google trends over the past five years using the keyword "Bullying in Schools," followed by an analysis of these trends through various scientific sources found via the Google Scholar search engine. Based on this analysis, it can be concluded that Civic Education contributes to creating an inclusive, safe, and respectful school environment, which is essential in preventing bullying. Through learning about Pancasila values, human rights, and social responsibility, students are taught to appreciate differences, develop empathy, and foster harmonious relationships with one another.